An ion-migration and electron-transfer cycle containing graphene and copper substrate analyzed with Raman spectra. (May 2017) - Lin, Weiyi; Zhuang, Pingping; Tian, Bo; Liu, Tie; Zhang, Cankun; Shih, Tien-mo; Cai, Weiwei
Abstract: Due to its semi-metallic characteristics, graphene may allow electron transfer to take place between itself and electrically-contacted metals. Here, we discover a two-component (graphene and copper) and two-process (ion migration and electron transfer) cycle, in which (a) electrons travel from the copper substrate to graphene based on Fermi-level variations through the interface, and (b) ions migrate vice versa due to Coulomb force via the intercalated electrolyte. To validate this proposed cycle, we scrutinize the copper-oxide formation, graphene-lattice phonon-frequency variations, and the morphological evolution of copper oxides, primarily via Raman measurements. Our study may provide the guidance for fundamental research on other graphene-metal assemblies as well as may enhance the versatility of graphene-based applications. Graphical abstract: Electrons transfer between graphene and electrically-contacted metals because of the former's semi-metallic characteristics. We discover a cycle comprising two components (graphene and copper) and two processes (ion migration and electron transfer). In this cycle, electrons travel from the copper to graphene based on Fermi-level variations, and ions migrate reversely via the intercalated electrolyte. To validate this proposed cycle, we investigate first the copper-oxide formation, then graphene-lattice phonon-frequency variations, and finally the morphological evolution of copper oxides via Raman and SEM measurements. Our study offers a guide for basic research on graphene-metal assemblies and broadens graphene-based applications.